Optimization of Cooperation Management Information System Against Public Information Service Effectiveness at Universitas Negeri Semarang - Diyanasari, Ledi; Noekent, Vitradesie; Setyanto, Adhi; Kurniawan, Ismail Okta (Universitas Negeri Semarang, 2022)
Based on Observation , The Cooperation Management Information System (SIM KS) was initially developed due to the need for data and information related to work unit activities at UNNES with external partners who have implemented agreements documented in formal legal documents of cooperation. SIM KS was developed to facilitate work units in digitally reporting and documenting cooperation documents that have been implemented with partner external . Information systems are used as data processors that can present structured data as an effort to provide information to the public, both internally and externally. Destination study this for analyze SIM KS optimization is limited effectiveness service information public . Study this is research using _ method combination Among quantitative and qualitative with object study is SIM KS and data collection techniques are carried out with observation to the system, deployment questionnaire and interview with system users . Data analysis techniques with use the TAM ( Technology Acceptance Model ) method. Research results this show that SIM KS optimization already enough effective in gift service information public in accordance with TAM constructs , namely perception convenience use , perception usability , attitude use technology , intention behavior for use as well as use technology actually . Effort necessary optimization _ upgraded is for give access to user external .